1998
DOI: 10.1046/j.1365-2508.1998.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and steroid receptors in endometrial polyps of postmenopausal patients under hormone‐replacement therapy

Abstract: Objective To study the histopathology of endometrial polyps that had developed during 6–18 months of hormone‐replacement therapy (HRT), and to determine the status of oestrogen and progesterone receptors in these lesions. Design Retrospective study. Subjects Fifty‐five menopausal patients receiving HRT who had endometrial polyps. Interventions Polypectomy followed by endometrial resection. Results Endometrial polyps have foci of hyperplasia that do not respond to progestin in menopausal patients receiving HRT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
2
22
0
2
Order By: Relevance
“…A positive correlation between unopposed estrogen and endometrial proliferation has been demonstrated histologically in both benign and malignant endometrium [14] . A limited number of studies have addressed ER and PR expression in endometrial polyps [2,7,10,15] . The higher expression of ER in postmenopausal endometrial polyps than atrophic endometrium in this and some other studies suggests a role for estrogen in the pathogenesis of endometrial polyps as a hyperplastic process.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between unopposed estrogen and endometrial proliferation has been demonstrated histologically in both benign and malignant endometrium [14] . A limited number of studies have addressed ER and PR expression in endometrial polyps [2,7,10,15] . The higher expression of ER in postmenopausal endometrial polyps than atrophic endometrium in this and some other studies suggests a role for estrogen in the pathogenesis of endometrial polyps as a hyperplastic process.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between estrogens, increased expression of endometrial hormonal receptors, (HRs) and endometrial stimulation is already accepted [8, 9]. In the last years it has been suggested that estrogens can cause the EPs growth by failure of proapoptotic mechanisms (an overexpression of Bcl-2 was reported in premenopausal and postmenopausal endometria) as well as by an increase in local levels of growth factors (GFs) such as fibroblastic GF, transforming GF-a, epithelial GF, IGF-1, and GF receptors within the endometrium which may promote polyp growth  [5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…There is also no unequivocality in pathogenic aspects. Some researchers believe EP are estrogen dependent tumors arising in conditions involving hyperestrogenemia [6]. Other authors attribute the formation of EP to an imbalance in the expression of estrogen and progesterone receptors [7].…”
Section: Analysis Of Published Data and Formulation Of Research Taskmentioning
confidence: 99%